Quantitative Detection of In-Service Strength of Underground Space Strata considering Soil-Water Interaction - Xiangfeng Lv; Hongyuan Zhou (Advances in Civil Engineering)
The in-service strength test of underground space strata is a hot issue in geotechnical engineering. In this study, we conducted mechanical analyses on the soil and the cutting bit involved in a rotary drilling process, which revealed the key factors influencing drilling. This allowed us to establish theoretical relationships among torque, propulsion, and soil strength parameters (i.e., unconfined compressive strength, shear strength, and cohesion). Moreover, with consideration of the effects of water content and geostatic stresses, we used an independently developed rotary drilling system with a 3D flexible boundary loading device to conduct 75 rotary drilling model indoor tests on silty clay in 15 groups. Based on the test results, we simplified the theoretical relationships and determined model parameters to obtain 15 quantitative relationships with 5 different water contents (4.8%, 9.7%, 14.8%, 19.6%, and 24.9%). Finally, through field application, we verified the quantitative relationships and we discussed their scope of application. The results showed it is feasible to predict the soil in-service strength based on rotary drilling parameters. Under the premise that water content is considered, the drilling parameters were found correlated linearly (correlation coefficients are all greater than 0.85) with strength parameters. In field application, absolute errors between the prediction and investigation results were less than 5%, satisfying engineering requirements.